2003
DOI: 10.3177/jnsv.49.447
|View full text |Cite
|
Sign up to set email alerts
|

Glucosyl Hesperidin Improves Serum Cholesterol Composition and Inhibits Hypertrophy in Vasculature

Abstract: Long-term administration of hesperidin (HES) or glucosyl hesperidin (GHES), a water-soluble analogue of HES, brings about an antihypertensive effect on spontaneously hypertensive rats (SHR). In the present study, we investigated the effects of long-term admin istration of HES and GHES (corresponding to 30mg/d/kg body weight) on serum lipid con centration and morphology of vasculature. Serum HDL cholesterol increased in both SHR and Wistar-Kyoto rats (WKY) fed a HES-or GHES-containing diet for 25wk. Simulta neo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
34
0
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 18 publications
1
34
0
2
Order By: Relevance
“…G-Hesperidin, a water-soluble derivative of hesperidin, has been shown to exhibit the same biological activities as hesperidin in vivo, [7][8][9] but the behavior of this derivative in the body remains to be fully clarified. In this study, we compared the metabolic fate and the bioavailability of G-hesperidin with those of hesperidin in rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…G-Hesperidin, a water-soluble derivative of hesperidin, has been shown to exhibit the same biological activities as hesperidin in vivo, [7][8][9] but the behavior of this derivative in the body remains to be fully clarified. In this study, we compared the metabolic fate and the bioavailability of G-hesperidin with those of hesperidin in rats.…”
Section: Discussionmentioning
confidence: 99%
“…6) Moreover, it has been confirmed that the biological activities of G-hesperidin are the same or more than those of hesperidin. [7][8][9] Nishizaki et al reported that G-hesperidin and hesperidin dose-dependently inhibited passive cutaneous anaphylaxis in rats, and that the effect of G-hesperidin was more continuous than that of hesperidin. 7) Furthermore, Chiba et al showed that Ghesperidin and hesperidin significantly prevented bone loss in the femur in ovariectomized mice.…”
mentioning
confidence: 99%
“…Our recent studies have shown that G-hesperidin as well as hesperidin exhibits such physiological activities as decrease of serum lipid peroxide level in hyperlipidemic mice (6), antihypertensive effect on spontaneously hypertensive rats ( 7,8) and suppression of passive cuta neous anaphylaxis in rats (9). These findings indicate that G-hesperidin behaves as hesperidin in the body and results in the exhibition of physiological activities.…”
Section: Discussionmentioning
confidence: 99%
“…A wide range of different biological activities, including antibacterial, antithrombotic, vasodilatory, antiinflammatory, and anticarcinogenic effects mediated by different mechanisms, are associated with flavonoid compounds (Middleton et al, 2000). Hesperidin reduced cholesterol and blood pressure (Ohtsuki et al, 2003) in rats. In a mouse study, large doses of the glucoside hesperidin decreased bone density loss (Chiba et al, 2003).…”
Section: Introductionmentioning
confidence: 99%